Management of School Operational Assistance Funds (BOS) to Enhance Extracurricular Activities at Yusuf Abdussatar Ibtidaiyah Madrasah, Kediri West Lombok - Ruba’i, Muhammad; Al Idrus, S. Ali Jadid; Thohri, Muhammad (Jurnal Ilmiah Profesi Pendidikan, 2024)
The School Operational Assistance Fund (BOS) plays a crucial role in Indonesian education, including at Madrasah Ibtidaiyah Yusuf Abdussatar in Kediri, West Lombok. This research explores the management of BOS to enhance extracurricular activities in the mentioned Madrasah. Qualitative methods were employed, utilizing data collection through observation, interviews, and documentary studies. The results indicate the effectiveness of BOS management through the RAPBM involving school principals, committees, and teachers. Extracurricular activities such as KKsQ, Scouting, and others are supervised and meet system standards. In conclusion, BOS management at Madrasah Ibtidaiyah Yusuf Abdussatar in Kediri effectively supports extracurricular activities, highlighting the crucial role of teachers as mentors. The implication is that an effective BOS management model can be applied in other schools to enhance extracurricular activities, strengthening the role of teachers in student mentoring beyond the regular curriculum.